1975
DOI: 10.1021/jo00896a013
|View full text |Cite
|
Sign up to set email alerts
|

Structural relations and interconversions of isomeric astilbins

Abstract: Reaction of Methyl 2-O-Benzoyl-3-0-methyl-4,6-di-Omethylsulfonyl-/$-D-mannopyranoside (10) with Potassium Benzoate in Refluxing JV,jV-Dimethylformamide (10 hr). An N, N-dimethylformamide solution (10 ml) containing 10 (105 mg, O. 22 mmol) and potassium benzoate (250 mg, 1.56 mmol) was heated at reflux for 10 hr. The precipitate was filtered off and the filtrate was evaporated in vacuo. The residue was chromatographed on silica gel (30 g). Elution with 7:1 benzene-ethyl acetate gave two fractions. The first fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

1975
1975
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 2 publications
2
22
0
1
Order By: Relevance
“…The chemical structures of all the five flavonoids as standards were also confirmed by 1 H NMR and 13 C NMR. The data of ESI-MS, 1 H NMR and 13 C NMR were consistent with those in the literature [25,26].…”
Section: Chemicals and Materialssupporting
confidence: 89%
“…The chemical structures of all the five flavonoids as standards were also confirmed by 1 H NMR and 13 C NMR. The data of ESI-MS, 1 H NMR and 13 C NMR were consistent with those in the literature [25,26].…”
Section: Chemicals and Materialssupporting
confidence: 89%
“…• Neoengeletin (4)/Neoisoengeletin (5) (8.3/1): 0.22% (Gaffield et al 1975). • Astilbin (6)/Neoastilbin (7) (1.2/1): 0.15% (Gaffield et al 1975;Xu et al 2005).…”
Section: Purification and Characterization Of Extractivesmentioning
confidence: 99%
“…• Astilbin (6)/Neoastilbin (7) (1.2/1): 0.15% (Gaffield et al 1975;Xu et al 2005). • p-Hydroxybenzoic acid (8): 0.09%.…”
Section: Purification and Characterization Of Extractivesmentioning
confidence: 99%
“…Their structures were elucidated using comprehensive spectroscopic methods including 1D and 2D NMR, MS, UV and IR, combined with a variety of chemical methods, and by comparison their data with those reported previously in the literature. The isolated compounds were involved in ten types of chemical structures, including fourteen flavonoid glycosides (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14), ten flavonoids (15)(16)(17)(18)(19)(20)(21)(22)(23)(24), four lignans (25)(26)(27)(28), seven phenolic acid compounds (29-34, 42), one steroid (35), one diterpene (36), one monoterpene (37), one phenolic glycoside (38), three iridoid glycosides (39)(40)(41) and one steroid saponin (43) ( Table 1). Among the isolated compounds, about of 50% of them were flavonoid glycosides and flavonoids, and it could be concluded that flavonoid glycosides, flavonoids, phenolic compounds and lignans were the major structure types in the EtOAc and n-BuOH fractions of SCP.…”
Section: Chemical Constituents Of the Etoac And N-buoh Fractions Frommentioning
confidence: 99%